Antileishmanial, insecticidal, anti-leukemic, phytotoxicity and anti-pancreatic lipase effects of ethanolic extracts of Moringa peregrina Seed - Albaayit, Shaymaa Fadhel Abbas; Maharjan, Rukesh; Abdullah, Rasedee; Mohd Noor, Mohd Hezmee; Ullah, Saeed; Al-Azzawi, Sura; Al-Khazraji, Husham Hussein Jasim (MS Editions, 2025)
In this study, the ethanolic extracts of Moringa peregrina seeds (MPSE) were evaluated for their antiparasitic, insecticidal, herbicidal, anti-leukemic, and anti-pancreatic lipase activities. The MPSE showed moderate antileishmanial activity against Leishmania major with an IC50 of 71.7 ± 0.46 μg/mL, compared to 10 ± 0.05 μg/mL and 4 ± 0.05 μg/mL for pentamidine and amphotericin B, respectively. The extract demonstrated moderate insecticidal activity with 41% mortality in Rhyzopertha dominica and 15.7% in Tribolium castaneum. MPSE exhibited potent herbicidal activity against Lemna minor at 1000 µg/mL. Additionally, MPSE inhibited the proliferation of leukemia K562 cells with an IC50 of 25 μg/mL and porcine pancreatic lipase with an IC50 of 83.7 ± 0.57 μg/mL. These findings suggest that MPSE may be beneficial as an antiparasitic, insecticidal, herbicidal, anti-leukemic, and anti-pancreatic lipase agent.